PERAN INTERNATIONAL COURT OF JUSTICE (ICJ) DALAM PENYELESAIAN KONFLIK ISRAEL-PALESTINA - Ilahi, Muhammad Alvi Rizki; Dasuki, Dasuki; Januarsyah, Putra Zenno (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
The dispute between Israel and Palestine has been going on for a long time, starting with the Balfour Declaration in 1917. This declaration contained support for the establishment of the state of Israel on Palestinian land. On October 7, 2023, an armed conflict occurred, Hamas carried out an attack by sending 3,100 rockets into Israel. Due to this action, Israel launched a retaliatory attack on Palestine, causing tens of thousands of casualties. The aim of this research is to elaborate on Israel's actions which do not comply with ICJ regulations regarding temporary measures as an effort to prevent genocide in Palestine and by carrying out this research it can be useful in providing new knowledge about the actions of a state actor and understanding how law enforcement in the Israeli-Palestinian armed conflict. These actions carried out by Israel gave rise to a new problem formulation regarding how the role of international law influences Israel's actions to comply with temporary measures issued by the ICJ.